PENGARUH KOMBINASI PICTURE AND PICTURE DAN TIME TOKEN TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Hersari, Hersari; Melati, Husna Amalya; Putra, Rody (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:The aims of this research were to find out the differences of activity and learning achievement of students who were given learning using combination between picture and picture and time token with students who were given learning using conventional methods, and the influence of using combination between picture and picture and time token toward activity and learning achievement of eleven grade students SMA Santun Untan Pontianak. This research was a quasi experiment (Quasi Exsperimental Design) research with Nonequivalent Control Group Design research, eleven grade students was divided into experiment class and control class. Calculations used U-Mann Whitney test showed that there are differences in student activity and learning achievement of control class and experimental class with the consecutive value were -2.69 <-1.96 and -3.25 <-1.96. Combination between picture and picture and time token learning gave high influence equal to 36.86% with ES equal to 1.12 Keywords: Time Token, Picture and Picture, Activity, Learning Achievement